Impact of training patterns on incidence of illness and injury during a women's collegiate basketball season - Anderson, L.; Triplett-McBride, T.; Foster, C.; Doberstein, S.; Brice, G. (The Journal of Strength and Conditioning Research, 2003)
This study was conducted to monitor the training patterns throughout a basketball season in order to determine if a relationship exists between the physical stress of practice and the occurrence of injuries and illnesses in NCAA Division III athletes. Subjects consisted of college women (n = 12) ranging in age from 18 to 22 years. A certified athletic trainer distributed a questionnaire following each practice, including 2 weeks of preseason, documenting the presence of injury, illness, or both, relative to the intensity and duration of practice. Training load, training monotony, and training strain were computed using the session rate of perceived exertion scale method. An increase in injuries occurred during times of increased training loads, particularly during the first 2 weeks of formal practice, and immediately subsequent to the holidays. The temporal relationship between training load and injury suggests a causative link (p < 0.01; r = 0.675). The present data suggest that the periodization pattern of basketball training may be linked to the likelihood of illness/injury.